The Effect of the Problem Based Learning Model Assisted by the Educandy Application on Student Learning Outcomes - Nabilah Syawali; Retno Mustika Dewi; Riza Yonisa Kurniawan (Universitas Negeri Semarang, 2026)
Despite the growing adoption of digital learning technologies, limited evidence exists regarding the integration of Problem-Based Learning supported by gamified educational applications in economics education. Grounded in active learning theory, this study examines the effect of a Problem-Based Learning approach assisted by the Educandy application on students’ learning outcomes. A quantitative study employing a quasi-experimental design with a nonequivalent control group was conducted. The experimental group received Problem-Based Learning supported by Educandy, whereas the comparison group participated in conventional instruction. Learning outcomes were measured using an achievement test, and the data were analyzed through descriptive and inferential statistical procedures. The findings indicate that students exposed to Problem-Based Learning assisted by Educandy achieved higher learning outcomes than those experiencing conventional learning. The results suggest that combining problem-centered learning with interactive digital media enhances student engagement and supports deeper understanding of economics concepts. This study contributes to the active learning literature by demonstrating the pedagogical value of integrating gamified learning applications with Problem-Based Learning and offers practical implications for educators seeking to improve learning effectiveness in economics classrooms.